The painter : a novel - Heller, Peter, 1959- (Alfred A. Knopf, 2014)
"A novel about an artist trying to outrun his past. Years ago, a well-known expressionist painter named Jim Stegner shot a man in a bar. The man lived, Jim served his time, and he has learned to live with the dark impulses that sometimes overtake him. Jim enjoys a quiet life in the valleys of Colorado. He works with a lovely model, he doesn't drink, he goes fly fishing in the evenings. His paintings fetch excellent prices at a posh gallery in Santa Fe. He is--if he can admit it--almost happy. One day, driving down a dirt road, Jim sees a man beating a small horse. Jim leaps out of the truck, tackles the man, and bloodies his nose. The man is Dell, a cruel hunting outfitter notorious among locals. Jim cannot shake his rage over the little horse. The next night, under a full moon, telling himself he is just going night fishing, he returns to the creek where Dell has his camp and kills him. As Jim tries to come to terms with what he has done, he must evade the police, navigate his own conscience, and escape the members of Dell's clan set on revenge. And he paints the whole time; trying to make sense of his actions. Traveling from the rough adobe cottages and rivers of Colorado to the bright streets and galleries of Santa Fe, aching with grief and transcendent with beauty, The Painter is a story about art and love and violence, and using the remnants of hardship to create a rich life"--